Evaluation And Performance Of Graphitic Carbon Nitride (g-C3N4) And Coconut Shell Husk Derived-Carbon Composite For Sonocatalytic Degradation Of Organic Dye - Keshavarthini, Ananadan (2023)
Wastewater is used water that has been polluted by home, industrial, and commercial use. The composition of wastewater is 99.9% water with the remaining 0.1% is what is removed. Dye wastewater is one of the huge environmental issues. The treatment of dye wastewater is an important matter for environmental and social sustainability. Conventional treatments are commonly used in Malaysia. However, this method has their own drawbacks such as, high operating cost and investment costs, long processing times, and large-scale operation feasibility. Thus, this research objective is to determine the optimum process condition for the sonocatalytic degradation of dye by using g-C3N4 and coconut shell husk (CSH) derived carbon composite and to elucidate the mechanism of sonocatalytic degradation of dye over g-C3N4 and coconut shell husk (CSH) derived carbon composite. Based on the results, it is feasible to synthesize carbon, (C) derived from CSH which can be used as solely photocatalyst in photocatalytic degradation of Methyl Orange (MO). In the results, it is found that g-C3N4, (CN) with 0.1 g/L catalyst loading at 5 ppm (20 min) has the highest photocatalytic activity with 88.07% of MO removal compared to C. In addition, alkaline conditions are more conducive for MO degradation. This study suggested that the concentration of MO can be reduced by utilizing Carbon derived from CSH. The implementation of eco-friendly raw materials introduces a more sustainable catalyst for the wastewater treatment process cost-effective which makes the utilization of the studied samples to have more practicality. According to Sustainable Developing Goal 6: Clean Water and Sanitation, we can improve water quality by reducing pollution, eliminating dumping, and minimizing release of hazardous chemicals and materials, halving the proportion of untreated wastewater and substantially increasing recycling and safe reuse globally.